Expression and Clinical Significance of Cancer Stem Cell Markers CD24, CD44, and CD133 in Pancreatic Ductal Adenocarcinoma and Chronic Pancreatitis - Durko, L. (Dis Markers, 2017)
Cancer stem cells (CSC) play an important role in pancreatic carcinogenesis and prognosis. The study aimed at examining the expression of CD24, CD44, and CD133 in human PDAC and CP in order to evaluate its clinicopathological correlations and the clinical significance. Surgical specimens from 23 patients with PDAC and 15 patients with chronic pancreatitis after pancreatic resection were stained with CD24, CD44, and CD133 antibodies. The intensity of staining was scored from 0 (negative) to 3 (strongly positive). Results. Mean CD24 staining score in PDAC was 1.38 ± 0.76 and was significantly higher than that in CP: 0.70 ± 0.53 (p < 0.01); CD44 score in PDAC was 2.23 ± 0.42 and was significantly higher than that in CP: 1.87 ± 0.55 (p < 0.05); CD133 score 0.93 ± 0.58 was not different from CP: 0.71 ± 0.43 (p > 0.05). CD44 immunoreactivity was significantly higher (p < 0.05) in pT1 and pT2 patients together as regards pT3: 2.45 ± 0.37 versus 2.06 ± 0.38 as well as in N0 patients compared to N1 patients: 2.5 ± 0.38 versus 2.04 ± 0.34. Conclusions. CD24 and CD44 are upregulated in human pancreatic cancer compared to chronic pancreatitis. CD44 immunoreactivity decreases with the tumor advancement and may represent the negative PDAC prognostic factor. Each CSC marker was differently related to PDAC advancement. CD133 may lack clinical significance in PDAC.